After Effects Breakdowns: N-Trig Commercial. - Stern, Eran (linkedin.com, 2016)
Glimpse behind the scenes of a real-world commercial made with After Effects. Learn how to decode a client brief, create animatics, and design the motion graphics in After Effects.